2019
DOI: 10.1002/bjs.11319
|View full text |Cite
|
Sign up to set email alerts
|

Short-term medical treatment of hypercalcaemia in primary hyperparathyroidism predicts symptomatic response after parathyroidectomy

Abstract: Background Primary hyperparathyroidism is often associated with non‐disease‐specific symptoms. The aim of this study was to evaluate whether normalization of hypercalcaemia with short‐term medical treatment can be used to predict the effects of parathyroidectomy and guide in surgical decision‐making. Methods This observational study included patients who received calcimimetic treatment for 4 weeks before parathyroidectomy (30–60 mg daily). A panel of tests was used to assess various aspects of quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The majority of indications for cinacalcet treatment are either for contraindication or refusal for surgery ( 19 , 21 , 22 , 24 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 35 , 36 , 39 , 43 ), reduction in serum Ca levels prior to surgery ( 18 , 20 , 26 , 27 , 31 , 40 , 41 ) or to treat refractory hypercalcemia despite parathyroidectomy ( 16 , 19 , 22 , 27 , 28 , 29 , 31 , 32 , 35 , 36 , 38 , 41 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of indications for cinacalcet treatment are either for contraindication or refusal for surgery ( 19 , 21 , 22 , 24 , 26 , 27 , 28 , 29 , 31 , 32 , 33 , 35 , 36 , 39 , 43 ), reduction in serum Ca levels prior to surgery ( 18 , 20 , 26 , 27 , 31 , 40 , 41 ) or to treat refractory hypercalcemia despite parathyroidectomy ( 16 , 19 , 22 , 27 , 28 , 29 , 31 , 32 , 35 , 36 , 38 , 41 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Literature review A total of 1301 articles were identified after duplicates removal, and eventually 28 articles were included in the review (16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43), of which 8 were conference proceedings (20,24,25,30,31,32,41,42) (Fig. 1).…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed inclusion and exclusion criteria are available through ClinicalTrials.gov (NCT 02227264). The cohort has been previously published and derives from a registry with comprehensive and biochemical workup, of which we extracted information regarding patient gender, age at surgery, tumor weight, and body mass index (BMI) as well as information regarding persistent or recurrent hyperparathyroidism following surgery [53].…”
Section: Institutional Control Cohortsmentioning
confidence: 99%
“…Thyroid disease is diagnosed in coincidence of PHPT in an increasing number of middle-aged people, in approximately 17-84% of PHPT patients in the form of nodules, thyroid cancer, or impaired thyroid hormone secretion 22 . Nonetheless, the relationship of PHPT biochemical parameters with the presence of non-classic symptoms has not been well established 23,24 . In relation to the above, the aim of this study is to characterize the clinical and biochemical profiles in symptomatic and asymptomatic Mexican patients with PHPT in a private hospital.…”
Section: Introductionmentioning
confidence: 99%